Comparison Between Thickness Design Based on Arahan Teknik Jalan 5/85 and 5/85 (2013) - Mohd Saidi, Muhammad Hafiz (Universiti Teknologi PETRONAS, 2017)
This Final Year Project is about the comparison of thickness design between ATJ 5/85 (1995) and ATJ 5/85 (2013). The comparison focused on the California Bearing Ratio design which changing the thickness of pavement for both manual. During this project, the sensitivity of CBR parameter has been analyzed according to the thickness of pavement for both manual. The thickness of pavement also compared based on different traffic volume which is low traffic volume, medium traffic volume and high traffic volume. Based on this study, the result shown where the thickness design based ATJ 5/85 (2013) must complied with CBR parameter more than 5%. Besides, the CBR parameter based on high traffic volume must be greater than 12%. As the CBR value is increase, the thickness of pavement is decrease as respectively. The CBR parameter must be considered in designing the thickness of pavement to overcome the pavement structure failure during the design period.